HB channel measurement and modeling in UWB for WBAN - Sanguanpuak, Chanidaphar; Bunlaksananusorn, Chanin; Promwong, Sathaporn (My University, 2019)
The combination of ultra-wideband and wireless human body application is a promising communication system for future wireless system in short range. In particular, wireless body area network is based on IEEE 802.15.6. Therefore, the effect with human body is very important to know a channel characterization. In this paper, the ling of sight and non-line of sight scenario have been presented. The measurement is coverage as a full-band of FCC regulation which is 3.1 GHz to 10.6 GHz and include the under test antenna and vector network analyzer is provided. In order to investigate some of parameter, path loss and power delay profile are discussion.
Keywords: Friis'; HB; Impulse radio; Transmission formula; UWB; WBAN